The relevance of mixed methods for network analysis in tourism and hospitality research. Issue 4 (27th February 2020) - Mariani, Marcello; Baggio, Rodolfo
Abstract : Purpose: Taking stock of extant hospitality and tourism research using social network analysis approaches, this study highlights why using either quantitative or qualitative approaches to examine social networks can be misleading and generate potentially biased findings. Indeed, purely qualitative and purely quantitative studies display limitations. The purpose of this study is to provide methodological insights by suggesting that mixed methods can be suitably used, depending on the specific research questions. Design/methodology/approach: The study consists of an analysis and critical discussion of the methods used in a number of papers leveraging social network approaches to study social networks in tourism and hospitality. The authors describe the benefits and limitations of each method studies considered are examined based on a number of aspects. Findings: More than half of the studies classified as network studies adopt quantitative designs and quantitative methods including statistical analyses and observational data. Mixed methods study is a minority and they are almost never labeled as mixed methods. A relevant portion of qualitative studies increasingly embeds a number of rudimentary statistical analyses. With an example, the authors also discuss that purely quantitative or purely qualitative methods can lead to discrepant results, and thus, the authors encourage scholars to embrace mixed method research designs such as explanatory or exploratory sequential designs. Advanced researchers might attempt in the future to embrace transformative, embedded or multiphase mixed methods. Research limitations/implications: This study is based on academic papers and research published before 2019. A rich research agenda is designed. Originality/value: This study contributes to explore the way social networks have been dealt with in tourism and hospitality research so far, by advancing a proposal to adopt mixed methods in the form of explanatory or exploratory sequential designs. To the best of the knowledge, it is the first study addressing methodological pitfalls in extant network-based research within the tourism and hospitality domain.